Transcatheter pulmonary valve replacement in congenital heart diseases - Adolphus Kai‐Tung Chau (Wiley, 2022)
ABSTRACT Surgical repair of a variety of congenital heart diseases involves repair of the right ventricular outflow tract (RVOT) with valved or non‐valved conduit to connect the right ventricle (RV) to the pulmonary artery (PA) or just patch enlargement of the native RVOT. With time, this RV‐PA conduit will degenerate with deterioration of function, either causing pulmonary stenosis or pulmonary regurgitation. This RVOT dysfunction may result in RV dilation, RV dysfunction, and eventual RV failure and arrhythmias. Multiple surgical pulmonary valve replacement (PVR) is often required throughout the patient's lifetime. Patients are subjected to increased risks with each additional cardiac operation. Transcatheter PVR (TPVR) has been developed over the past two decades as a valuable non‐surgical alternative to restore the RVOT and RV function, and hence reduce patients' lifetime risks related to surgery. This article will discuss the long‐term results of TPVR which are demonstrated to be comparable to surgical results and the latest development of large pulmonary valves which will allow TPVR to be performed on native or larger RVOT.